Global epidemiology of acromegaly: a systematic review and meta-analysis - Crisafulli, Salvatore; Luxi, Nicoletta; Sultana, Janet; Fontana, Andrea; Spagnolo, Federica; Giuffrida, Giuseppe; Ferraù, Francesco; Gianfrilli, Daniele; Cozzolino, Alessia; Cristina De Martino, Maria; Gatto, Federico; Barone-Adesi, Francesco; et al. (European journal of endocrinology, 2021)
To date, no systematic reviews and meta-analysis on the global epidemiology of acromegaly are available in the literature. The aims of this study are to provide a systematic review and a meta-analysis of the global epidemiology of acromegaly and to evaluate the quality of study reporting for the identified studies. MEDLINE, EMBASE and The Cochrane Library databases were searched for studies assessing the epidemiology of acromegaly from inception until 31 January 2020. We included original observational studies written in English, reporting acromegaly prevalence and/or incidence for a well-defined geographic area. Two reviewers independently extracted data and performed quality assessments. Prevalence and incidence pooled estimates were derived by performing a random-effects meta-analysis. A total of 32 studies were included in the systematic review, and 22 of them were included in the meta-analysis. The pooled prevalence of acromegaly was 5.9 (95% CI: 4.4-7.9) per 100 000 persons, while the incidence rate (IR) was 0.38 (95% CI: 0.32-0.44) cases per 100 000 person-years. For both prevalence and IR, considerable between-study heterogeneity was found (I2 = 99.3 and 86.0%, respectively). The quality of study reporting was rated as the medium for 20 studies and low for 12 studies. Although the largest amount of heterogeneity was due to the high precision of the studies' estimates, data source and geographic area could represent relevant study-level factors which could explain about 50% of the total between-study variability. Large-scale high-quality studies on the epidemiology of acromegaly are warranted to help the public health system in making decisions.